Exploring the relationship between workplace bullying and objective cognitive performance. - Tuckey, Michelle R.; Li, Yiqiong; Huisy, Gina; Bryan, Janet; de Wit, Adele; Bond, Stephanie (Work & Stress)
In two studies, we investigated the effects of workplace bullying on objective measures of cognitive functioning. In Study 1, 47 university employees, self-identified as current targets of bullying (n = 24) or non-targets (n = 23), completed objectively scored cognitive tasks assessing general attention and three components of working memory (central executive, visuospatial sketchpad, and phonological loop). T-test analyses showed that self-identified targets performed more poorly on the suite of tests compared to non-bullied counterparts, primarily driven by deficits in central executive functioning. Study 2 recruited 70 retail and hospitality workers who completed the cognitive tasks plus measures of preoccupying cognitions and exposure to negative acts. As hypothesised, we found significant indirect effects demonstrating that preoccupying cognitions explained the negative relationship between bullying and the three aspects of working memory. The magnitude of the cognitive deficits observed here, and their potential significance for job performance, highlights the importance of primary bullying prevention within organisations. Secondary and tertiary prevention efforts should also consider cognitive impairments experienced by targets and look for opportunities to reduce preoccupying cognitions, which compete for limited cognitive resources, to mitigate the erosive effects of bullying.